Proteome-wide analysis of neural stem cell differentiation to facilitate transition to cell replacement therapies. (February 2014) - Zizkova, Martina; Sucha, Rita; Tyleckova, Jirina; Jarkovska, Karla; Mairychova, Katerina; Kotrcova, Eva; Marsala, Martin; Gadher, Suresh Jivan; Kovarova, Hana
<x xml:space="preserve">Abstract</x> Neurodegenerative diseases are devastating disorders and the demands on their treatment are set to rise in connection with higher disease incidence. Knowledge of the spatiotemporal profile of cellular protein expression during neural differentiation and definition of a set of markers highly specific for targeted neural populations is a key challenge. Intracellular proteins may be utilized as a readout for follow-up transplantation and cell surface proteins may facilitate isolation of the cell subpopulations, while secreted proteins could help unravel intercellular communication and immunomodulation. This review summarizes the potential of proteomics in revealing molecular mechanisms underlying neural differentiation of stem cells and presents novel candidate proteins of neural subpopulations, where understanding of their functionality may accelerate transition to cell replacement therapies.